2014
DOI: 10.3126/njog.v9i1.11191
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma Arising in Mature Cystic Teratoma of the Ovary

Abstract: Malignant transformation of mature germ cell teratoma is rare and has been reported sporadically. Any of the constituent tissue of a teratoma has the potential to undergo malignant transformation. Squamous cell carcinoma is the most common transformation and is derived from the metaplastic squamous epithelium of teratoma. We are reporting a case of 65 years old postmenopausal women with squamous cell carcinoma arising in mature cystic cell teratoma of the ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…In our present case also, some thickened or solid parts in the cyst wall were identified on gross examination of surgical pathology specimen. Other studies like those done by Bashyal R et al [3] , by Gupta N et al [4] , by Gupta V et al [10] , by Santwani PM et al [6] and by Maharjan S [15] also show similar findings in gross examination of the tumor specimen itself. Finally, we can say that the teratomas with larger size & variable cyst-wall thickness with thickened or solid area (parts) grossly visible in the cyst-wall have maximum chance of malignant transformations.…”
Section: Table 3: Comparative Evaluation Of Tumor Size Of Different Ssupporting
confidence: 71%
See 3 more Smart Citations
“…In our present case also, some thickened or solid parts in the cyst wall were identified on gross examination of surgical pathology specimen. Other studies like those done by Bashyal R et al [3] , by Gupta N et al [4] , by Gupta V et al [10] , by Santwani PM et al [6] and by Maharjan S [15] also show similar findings in gross examination of the tumor specimen itself. Finally, we can say that the teratomas with larger size & variable cyst-wall thickness with thickened or solid area (parts) grossly visible in the cyst-wall have maximum chance of malignant transformations.…”
Section: Table 3: Comparative Evaluation Of Tumor Size Of Different Ssupporting
confidence: 71%
“…Name of the study Year of publication Numbers of cases reported Age of occurrence Santwani PM et al [6] 2008 01 40 years Gupta V et al [10] 2009 02 30 years, 65 years Bashyal R et al [3] 2012 03 33 years, 51 years, 60 years Suna Avc1 et al [9] 2012 01 52 years Gupta N et al [4] 2014 01 65 years Ranu Patni [11] 2014 01 53 years Mardi K et al [12] 2014 01 68 years Yarmohammadi H et al [13] 2014 01 48 years Rekhi B et al [14] 2015 12 Median age = 49 years Sharma S et al [1] 2015 01 66 years Abhilasha N et al [8] 2016 10 Median age = 53.5 years Srivastava H et al [2] 2017 01 30 years Goudeli C et al [7] 2017 01 54 years ~ 323 ~ Indulkar ST et al [5] 2018 01 40 years Maharjan S [15] 2019 In our present study, painful enlargement or distension of abdomen is the presenting complaint of the patient herself. Similar complaints have been reported in other case studies also like those done by Bashyal R et al [3] , by Gupta N et al [4] , by Santwani PM et al [6] , etc. Some authors also reported other complaints like constipation, loss of appetite, loss of weight, low grade fever, etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations